Prevalence of hepatitis B infection and its associated factors among pregnant mothers attending antenatal care at public hospitals at Hararghe, Eastern Ethiopia - Umer, Abbas; Teklemariam, Zelalem; Ayele, Firayad; Mengesha, Melkamu Merid (Frontiers in Global Women's Health, 2023)
Background: Hepatitis B infection is among the leading public health problems with significant morbidity and mortality globally. The risk of developing chronic infection and estimated to be 90% prenatally resulting in maternal complications and poor neonatal or infant outcomes. Its infectivity is a hundred times higher than Human Immunodeficiency Virus yet it obtains little attention in public health. Therefore, this study was conducted to assess the Prevalence of Hepatitis B infection and Its Associated Factors among Pregnant Mothers Attending Antenatal Care at public hospitals in West Hararghe, Eastern Ethiopia 2020. Method: Institution-based cross-sectional study was conducted on 300 pregnant mothers selected by systematic random sampling from September to December 2020. Data were collected by face-to-face interview using a pretested structured questionnaire. A blood sample was collected and tested for Hepatitis B surface antigen using the Enzyme-Linked Immunosorbent Assay test method. Data were entered into EpiData version 3.1 and exported to Statistical Package for the Social Science version 22 for analysis. Bivariate and multivariable logistic regressions were used to assess the association between outcome and predictor variables. P-value <0.05 was considered to be statistically significant. Results: The overall seroprevalence of Hepatitis B virus infection was 8% (95%, CI: 5.3-11.0) among pregnant mothers. History of tonsillectomy (AOR=5.7; 95% CI: 1.3-23.9), tattoo (AOR=4.3; 95% CI: 1.1, 17.0), having multiple sexual partners (AOR=10.8; 95% CI: 2.5, 45.9) and history of contact with jaundiced patients (AOR=5.6; 95% CI: 1.2, 25.7 were factors associated with seroprevalence of Hepatitis B virus infection among pregnant mothers. Conclusion: The prevalence of the hepatitis B virus was highly endemic. History of having tonsillectomy, tattooing, having multiple partners and history of contact with jaundiced patients were factors associated with hepatitis B virus infection. Therefore, hospitals, districts, and regional health departments should establish programs on health education both at the health facility and community about hepatitis B virus modes transmission and prevention by focusing on the identified factors.